Retranslation as Feminist Re-visioning: La casa de los espíritus into Brazilian Portuguese - Berton-Costa, Pâmela [UNESP] (Universidad de Antioquia, 2020)
There has been renewed interest in feminist translation studies in recent years; however, debate continues about the best approach to effectively apply feminist strategies to translation, especially when it comes to literary texts. In this paper, using examples from a previous comparison between the original book La casa de los espíritus and the only Brazilian Portuguese translation, feminist retranslation options are discussed. Although this novel, by Chilean author Isabel Allende, is part of the Latin American Post-Boom, which many critics consider to be a feminist literary movement, the translation seems to consistently erase the novel’s feminist features. This paper attempts to show that a feminist literary retranslation may highlight characteristics of a text that had been overlooked. It is important to bear in mind that this study does not intend to “correct a bad translator,” but to reflect upon the role of the feminist translator.
La retraducción como acto de re-visión feminista: La casa de los espíritus al portugués brasileño
La retraduction comme ré-vision féministe: La casa de los espíritus au portugais brésilien
Keywords: Brazilian Portuguese; Feminist retranslation; Latin America; Literary translation; Post-Boom